2005
DOI: 10.1300/j083v46n02_06
|View full text |Cite
|
Sign up to set email alerts
|

Anticipated and Experienced Changes in Activities After Husbands Retire

Abstract: As an element of anticipatory socialization, ability to predict future roles accurately may impact subsequent adaptation. Part of a larger study of retirement and marital quality, this longitudinal research examined husbands' and wives' (n = 61 couples) anticipations of change (more/less/same) in six individual and joint activities following husbands' retirement, and compared them with couples' reported experiences a year after husbands had retired. With the exception of household tasks, continuity in levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The new distribution of domestic tasks discussed by the participants was also supported by the literature. Fitzpatrick et al (2005) suggested that household task sharing undergoes the most change after retirement. Most participants in this study were neutral in their feelings towards this change, but one of them did identify some difficulty adjusting to his new role at home.…”
Section: Discussionmentioning
confidence: 99%
“…The new distribution of domestic tasks discussed by the participants was also supported by the literature. Fitzpatrick et al (2005) suggested that household task sharing undergoes the most change after retirement. Most participants in this study were neutral in their feelings towards this change, but one of them did identify some difficulty adjusting to his new role at home.…”
Section: Discussionmentioning
confidence: 99%
“…Miller (2000) concluded that couples tend to adapt to changes in their circumstances, such as retirement, as a result of an underlying tendency toward stability. As a potential explanation, Fitzpatrick, Bushfield, and Vinick (2005) found that contrary to the couples' own expectations, there was significant stability in couples' individual and couple activities. Thus, although many couples expect their lives to be different after retirement, their lives are remarkably similar to when they were still working.…”
Section: Lack Of Support For a Link Between Retirement And Marital Qu...mentioning
confidence: 76%
“…This approach allows us to study discrepancies between partners' expectations and experiences, testing whether, on average, partners experience more, or rather less problems than initially expected. Moreover, by taking this approach we are able to examine whether expectations are predictive of outcomes on the same dimension (this congruence may only be modest, as for instance has been shown for changes in activities upon retirement, e.g., see Fitzpatrick, Bushfield, & Vinick, 2005), and whether there are cross-over effects (i.e. whether expectations on one dimension are related to the experiences on another dimension).…”
mentioning
confidence: 99%